Greenspace, stress, and health: how is epigenetics involved? - Ugoji Nwanaji-Enwerem; John E. McGeary; John E. McGeary; Diana S. Grigsby-Toussaint; Diana S. Grigsby-Toussaint (Frontiers Media S.A., 2024)
Most expositions of the association between green space and overall health and well-being focus on psychosocial mechanisms. However, discussions of the biological underpinnings of the exposure to green space and health implications are limited. In this paper, we highlight the role epigenetics plays in the manifestation or suppression of stress, in addition to some of the proposed epigenetic mechanisms through which green space mitigates stress. The Health: Epigenetics, Greenspace and Stress (HEGS) model is introduced to explicate this association, and suggestions for research to build the evidence base in this area are discussed.